Improving The Ability To Recognize Object Through Flip Chart For Deaf Children (Single Research Subject in SLB Al-Ishlaah, Padang City) - Welgiana Mitra; Damri Damri (Edumaspul: Jurnal Pendidikan, 2022)
This research is motivated by the problems that researchers found at SLB Al-Ishlaah Padang, a deaf child with the initial A has not been to recognize object in the surrounding environment. Based on this, this study aims to improve the ability to recognize objects correctly and see if this flip cahrt media can have a positive impact. This study uses an experimental approach in the form of singgle subject research (SSR) with an A-B-A design. The assessment in this study is consistent with measuring the correct number of objects. The results of this study indicate that the ability of deaf children to recognize objects increases, in the initial baseline conditions carried out four times the child is only able to know four objects, namely mirrors, keys, tables and clocks correctly. In the intervention condition or when given the observed treatment. During the five meetings the child’s ability increased, the child was able to recognize six objects, namely lamps, mirrors, keys, tables, clocks and brooms. Then, at the final baseline the child’s ablity to recognize objects remained good. The result of this study prove that the use of flip chart media can improve the ability to recognize objects in deaf children.